2022
DOI: 10.3390/polym14214526
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Polyurethane Biofoams Filled with Chemically Compatible Fruit Peels

Abstract: Banana and bergamot peels are underutilized byproducts of the essential oil and juice-processing industry. This study was designed for the development of rigid polyurethane foam (RPUF) composites using polysaccharide-rich fruit peels as fillers. These fillers were characterized for chemical properties using wet analyses. Additionally, the influences of the filler type and filler content on morphological, thermal, mechanical, hygroscopic, and colorimetric properties of the RPUF were investigated. The main resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It was assumed that the incorporation of either LigW or LigW/LG particles weakened the cellular structure of the resulting products due to solid particles located in cell walls and mostly the porous impurities of LigW particles. Additionally, our results showed that using the higher ratio of LigW and LG resulted in higher compressive values obtained at the same apparent density of the bioPUR foam composites, which was related to the cross-link formation between LG-coated LigW fillers and the bioPUR foam polymeric matrix [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was assumed that the incorporation of either LigW or LigW/LG particles weakened the cellular structure of the resulting products due to solid particles located in cell walls and mostly the porous impurities of LigW particles. Additionally, our results showed that using the higher ratio of LigW and LG resulted in higher compressive values obtained at the same apparent density of the bioPUR foam composites, which was related to the cross-link formation between LG-coated LigW fillers and the bioPUR foam polymeric matrix [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in strength of the bioPUR foams modified with LigW/LG 1:1 and LigW/LG 1:2 compared to bioPUR foams modified with LigW particles is related to the formation of cross-links between compatible fillers and the bioPUR matrix. This mechanism was studied and reported in a few studies as being able to induce a gain in some mechanical properties [ 46 , 47 , 48 ], although such filler–matrix interactions may not be strong enough to impart increases in mechanical performance and overcome the strength of control bioPUR foams, as the filler particles attach themselves to the cell walls, encapsulating blowing gas, and turn into nucleation sites, which weaken, and even damage, the edges of cells due to the weaker interaction between hydroxyl groups on the surface of the particles and isocyanate groups.…”
Section: Resultsmentioning
confidence: 99%
“…For the RPUFs manufacture, castor oil (24 parts/g), distilled water, glycerol (8 parts/g), PEG-400 (3.5 parts/g), silicon oil (1 parts/g) and filler were mechanically mixed at 1000 rpm for 120 s. Thereafter, p-MDI (63 part/g) and amine (0.4 part/g) were added to the other components, which were then mechanically stirred for an extra 60 s, keeping a constant NCO/OH stoichiometric ratio of 1.2. The detailed formulation of the manufactured RPUFs is presented in Table 1, according to others' research from the group [16,22]. After this process, the liquid reaction mixture was cast in an open mould to freely rise (Figure 1).…”
Section: Rigid Polyurethane Foam Manufacturingmentioning
confidence: 99%
“…Based on the mechanical and hygroscopic performances achieved, these authors reported that the wood flour was the most promising filler due to its high holocellulose content. Finally, in the most recent research paper of the group [16], the incorporation of two fruit peels (from banana and bergamot) as fillers in RPUFs yielded increases in cell size and thermal stability. However, there are many residues from the food industry that could be used as fillers in RPUFs, due to their high content of hydroxyls associated with amorphous polysaccharides.…”
Section: Introductionmentioning
confidence: 96%